Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702558
|View full text |Cite
|
Sign up to set email alerts
|

Data-in-Place

Abstract: We present findings from a year-long engagement with a street and its community. The work explores how the production and use of data is bound up with place, both in terms of physical and social geography. We detail three strands of the project. First, we consider how residents have sought to curate existing data about the street in the form of an archive with physical and digital components. Second, we report endeavours to capture data about the street's environment, especially of vehicle traffic. Third, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(56 citation statements)
references
References 23 publications
1
55
0
Order By: Relevance
“…It was easy to deduce if individuals were walking straight to offices, lingering in the lobby, were new visitors to the building, or if events were taking place. While previous research shows the benefit of locally embedded visualisations [41], and ambiguous information to support personal interpretation about behaviours [44], we present the potential for low-level behavioural information to convey higher-level meaning when displayed in-situ.…”
Section: Rq1mentioning
confidence: 56%
See 1 more Smart Citation
“…It was easy to deduce if individuals were walking straight to offices, lingering in the lobby, were new visitors to the building, or if events were taking place. While previous research shows the benefit of locally embedded visualisations [41], and ambiguous information to support personal interpretation about behaviours [44], we present the potential for low-level behavioural information to convey higher-level meaning when displayed in-situ.…”
Section: Rq1mentioning
confidence: 56%
“…It is likely that ambiguity in walking trajectories would also support individuals in creating personal meaning from the visualisation. Whilst in Williamson and Brewster's system [44] the observer was displaced from the performer, presenting information locally, in the place it refers to, can better support the interpretation of both [21,27,41]. In a behaviour change study, designed to encourage building occupants to use the stairs rather than an elevator, Rogers et al [38] found situated an ambient displays of raised and lowered balls provoked reflection and behaviour change, despite ambiguity in the visualisation.…”
Section: Walking Trajectories As a Reflection Of Public Practicementioning
confidence: 99%
“…For this reason, HCI research has a long history of considering the role of technology at the neighbourhood scale, often through long-term engagement with neighbourhoods to create meaningful interventions that reflect the unique characteristics of the people and places they are designed for [e.g. 6,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have increasingly investigated the stories people tell themselves, and each other with data. Taylor et al [11] provide a description of 'data-in-place' to detail how social, cultural, political and historical contexts are key -how data comes to be situated, to matter and to settle in a place.…”
Section: Introductionmentioning
confidence: 99%